Non‐invasive detection of portal hypertension by enhanced liver fibrosis score in patients with different aetiologies of advanced chronic liver disease. (18th May 2020) - Simbrunner, Benedikt; Marculescu, Rodrig; Scheiner, Bernhard; Schwabl, Philipp; Bucsics, Theresa; Stadlmann, Alexander; Bauer, David J. M.; Paternostro, Rafael; Eigenbauer, Ernst; Pinter, Matthias; Stättermayer, Albert Friedrich; Trauner, Michael; et al.
Abstract: Background and Aims: The enhanced liver fibrosis (ELF) score comprises serum markers of fibrogenesis and matrix remodelling and was developed to detect liver fibrosis, however, it may also be useful for the non‐invasive detection of portal hypertension (PHT). Methods: ELF score and its single components (TIMP1/PIIINP/HA) were analysed in 201 patients with advanced chronic liver disease (ACLD; ie hepatic venous pressure gradient (HVPG) ≥6 mm Hg). Patients with pre‐/post‐hepatic PHT, hepatocellular carcinoma beyond Milan criteria, and history of TIPS implantation or liver transplantation were excluded. Results: ELF and its single components correlated with HVPG in the overall cohort: ELF: r  = .443, TIMP1: r  = .368, PIIINP: r  = .332, and HA: r  = .419 (all P  < .001). The strength of the correlation between ELF and HVPG decreased in higher HVPG strata: 6‐9 mm Hg: r  = .569( P  = .004), 10‐19 mm Hg: r  = .304 ( P  = .001) and ≥20 mm Hg: r  = −.023( P  = .853). Area under the receiver operating characteristics (AUROC) of ELF score to detect clinically significant PHT (CSPH; HVPG ≥ 10 mm Hg) was 0.833. Importantly, HA alone yielded an AUROC of 0.828. Detection of CSPH in strictly compensated ACLD (cACLD) patients was less accurate: AUROC: 0.759 ( P  < .001). CSPH was ruled‐in by ELF ≥ 11.1 with a PPV of 98% (sensitivity: 61%/specificity: 92%/NPV:24%), but CSPH could not be ruled‐out. ELF score had a low AUROC of 0.677 (0.60‐0.75; P  < .001) for the diagnosis of high‐risk PHT (HRPH; HVPG ≥ 20mm Hg) and, thus, HRPH could not be ruled‐in by ELF. However, ELF < 10.1 ruled‐out HRPH with a NPV of 95% (sensitivity: 97%/specificity: 26%/PPV: 39%). Conclusion: The ELF score correlates with HVPG at values <20 mm Hg. An ELF ≥ 11.1 identifies patients with a high probability of CSPH, while an ELF < 10.1 may be used to rule‐out HRPH.